The expression of p53, Rb, and c-myc protein in cervical cancer by immunohistochemistry stain - ADI PRAYITNO; RUBEN DARMAWAN; ISTAR YULIADI; AMBAR MUDIGDO (Society for Indonesian Biodiversity, 2005)
The pathogenesis of cancer as whole (50%) is caused by gene mutation. Pathogenesis of cervical cancer has focusing on Human Papilloma Virus (HPV). Early-7 (E7) proteins of HPV shell bind the Rb tumor suppressor gene, so pRb (Rb protein) can’t express. Because of the E2F transcription factor gene can’t bound with pRb, so E2F gene are going active and help c-myc for DNA replication and to stimuli the cell cycle. E6 protein of HPV is bind to and facilitates the degradation of the p53 tumor suppressor gene product. The objective of this experiment is to known the expression of p53, Rb and c-myc proteins in cancer of uterine cervix. Nineteen blocks paraffin tissue of cervical cancer are cut in thoroughly cleaned cryotome and place in glass plate that covered with poly-elysine. The immunohistochemistry is done with monoclonal antibody anti p53, Rb and c-myc proteins. The Result of this experiment is shown that the expression of proteins of p53 protein is 40%, Rb protein is 30.8% and c-myc protein is 50.1%. The conclusion from this experiment is that the expression of p53, Rb and c-myc proteins in cervical cancer are in mild category (30-70%). The experiment about cervical cancer is suggested.Key words: cervical cancer; p53; Rb; c-myc; immunohistochemistry.